- Cultivation of Acem acem (Oxalis dehradunesis Raizada) and Its Utilization as a Hand Sanitizer for Protection of Exposure to Chemical Pesticides: - - Hasanah, Yaya (Talenta Publisher Universitas Sumatera Utara, 2022)
Farmers in Tanah Karo still use chemical pesticides a lot and often experience direct exposure to pesticides due to not using personal protection during pesticide spraying. Based on the farmers' habits, exposure to pesticides is cleaned by rubbing the leaves of acem acem (Oxalis dehradunensis Raizada) to the dirty and exposed parts of the pesticide. Acem acem leaves have many benefits and are local potentials that can be new opportunities for farmers to process acem acem leaves into products that have economic value. In addition, acem acem leaves that grow wild and are scattered in every farmer's field in Tanah Karo become an obstacle in providing raw materials in large quantities because it will take a lot of time, effort, and money to collect them. The purpose of this community partnership program is to develop acem acem leaves as raw material for hand sanitizers by means of intensive cultivation, increase farmers' understanding of the use of acem acem leaves in protecting exposure to chemical pesticides, empower farming communities in making hand sanitizers made from acem acem leaves. The solution to partner problems is to cultivate acem acem as raw materials, educate the farming community to utilize acem acem leaves into products that have economic value such as hand sanitizers so that they can increase farmers' income. The implementation of community partnership service activities is carried out by training at each stage of acem acem cultivation, maintenance of acem acem, harvesting, and post-harvest as well as processing acem acem into hand sanitizers, as well as direct practice of demonstration plots for acem acem cultivation.